Efektivitas Pembelajaran Kolaboratif dalam Meningkatkan Pemahaman Mekanika Teknik Siswa Jurusan DPIB - Salsabila, Fairuza Putri Rahmah; Sutrisno, Sutrisno (Paedagogie, 2026)
Most DPIB students consider Engineering Mechanics as a scary subject and tend to be a burden, so students often find it difficult to understand the lesson. One of the factors causing students to find it difficult to understand Engineering Mechanics is the way the teacher delivers the lesson. One learning model that can be used to support Engineering Mechanics learning is a collaborative learning model by dividing students into small groups and working together to solve a problem by exchanging ideas. Through this learning model, it is expected that students' interest and motivation can increase in learning activities. This study aims to measure the effectiveness of collaborative learning when applied in Engineering Mechanics learning for class X DPIB at SMKN 11 Malang compared to conventional learning. The sample consisted of 30 class X DPIB students of SMKN 11 Malang. Data collection was carried out using an Engineering Mechanics problem-solving ability test instrument which was divided into a pre-test and a post-test. The results of the data analysis showed that the significance value of the covariance analysis test was greater than the significance value level so that H0 was rejected and Ha was accepted. Thus, it can be concluded that the collaborative learning model is effective in improving the understanding of Engineering Mechanics in class X DPIB students at SMKN 11 Malang.